2008
DOI: 10.1016/j.febslet.2008.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin enhances insulin signaling and potentiates insulin‐stimulated glucose uptake in 3T3‐L1 adipocytes

Abstract: To explore a novel adipokine, we screened adipocyte differentiation-related gene and found that TIG2/chemerin was strongly induced during the adipocyte differentiation. Chemerin was secreted by the mature 3T3-L1 adipocytes and expressed abundantly in adipose tissue in vivo as recently described. Intriguingly, the expression of chemerin was differently regulated in the liver and adipose tissue in db/db mice. In addition, serum chemerin concentration was decreased in db/db mice. Chemerin and its receptor/ChemR23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(181 citation statements)
references
References 30 publications
(40 reference statements)
8
161
2
6
Order By: Relevance
“…Many in vitro studies have reported the effects of the chemerin/ChemR23 system on adipocytes. Chemerin has been proposed to control the differentiation of 3T3-L1 preadipocytes via ChemR23 (Bozaoglu et al 2007, Goralski et al 2007, Roh et al 2007, to promote lipolysis (Roh et al 2007), and to potentiate insulin-stimulated glucose uptake in adipocytes (Takahashi et al 2008). Taken together, these previous studies indicate a role for the chemerin/ ChemR23 system in adipose tissue function and metabolism.…”
Section: Introductionsupporting
confidence: 56%
“…Many in vitro studies have reported the effects of the chemerin/ChemR23 system on adipocytes. Chemerin has been proposed to control the differentiation of 3T3-L1 preadipocytes via ChemR23 (Bozaoglu et al 2007, Goralski et al 2007, Roh et al 2007, to promote lipolysis (Roh et al 2007), and to potentiate insulin-stimulated glucose uptake in adipocytes (Takahashi et al 2008). Taken together, these previous studies indicate a role for the chemerin/ ChemR23 system in adipose tissue function and metabolism.…”
Section: Introductionsupporting
confidence: 56%
“…Although chemerin is among the adipokines that are present at statistically lower levels in "insulin sensitive-" obese individuals than "insulin resistant-" obese individuals (Klöting et al, 2010), several in vitro studies have produced conflicting results. Some research groups have shown that in the 3T3-L1 cell line, increased chemerin expression resulted in increased insulininduced IRS1 tyrosine phosphorylation and glucose uptake (Takahashi et al, 2008); however, other groups have demonstrated the reverse in the same cell line, where chemerin significantly decreased insulin stimulated-glucose uptake, indicating insulin resistance (Kralisch et al, 2009). Furthermore, there have been reports with conflicting results where chemerin expression was examined as a function of insulin sensitivity in response to thiazolidinediones (TZDs).…”
Section: Discussionmentioning
confidence: 99%
“…Later studies characterized chemerin as an adipokine with a potential role in regulating adipocyte development in vitro and metabolic functions, such as glucose and lipid metabolism, in adipose tissue (Goralski et al, 2007). Chemerin has been shown to affect insulin signaling in 3T3-L1 adipocytes (Kralisch et al, 2009;Takahashi et al, 2008). Compared with lean animals, chemerin gene expression is elevated in the adipose tissue of obese animals, and expression levels are markedly elevated during the differentiation of 3T3-L1 cells into mature adipocytes (Bozaoglu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…62 Vaspin is a serine protease inhibitor and is reported to reduce expression of leptin, resistin and TNFα and improves insulin sensitivity. 63,64 The recently discovered adipokine chemerin 65,66 increases insulin sensitivity in 3T3-L1 adipocytes 67 and is essential for normal adipocyte differentiation. 65,66,68 However, it has also been shown to lower glucose tolerance in murine models of obesity/ diabetes 69 and to cause insulin resistance in human skeletal muscle cells, where it was also observed to be pro-inflammatory.…”
Section: Adipose Tissue a Paracrine And Endocrine Organmentioning
confidence: 99%